2009
DOI: 10.1111/j.1095-8649.2008.02117.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and mortality of European glass eel Anguilla anguilla marked with oxytetracycline and alizarin red

Abstract: The growth and mortality of European glass eel Anguilla anguilla 192 days after marking with oxytetracycline and alizarin red S were not significantly different between the two treatments and not different to the unmarked A. anguilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 20 publications
5
37
3
Order By: Relevance
“…Tributaries, lakes and ponds with low or no natural immigration have been stocked using glass eels and elvers caught in river estuaries (Walter, 1910;Mu¨ller, 1975;Klein-Breteler et al, 1990;Simon et al, 2009) and farm eels (Wickstro¨m et al, 1996;Pedersen, 1998Pedersen, , 2000Pedersen, , 2009Simon et al, 2013). The annual length increases and survival rates in the stocked eels vary strongly between the stocking environments, the stocking materials (farm and glass eels), the stages (smaller and larger eels) and times after stocking (Bisgaard and Pedersen, 1991;Pedersen, 1998;Lin et al, 2007;Simon et al, 2013;Simon and Do¨rner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tributaries, lakes and ponds with low or no natural immigration have been stocked using glass eels and elvers caught in river estuaries (Walter, 1910;Mu¨ller, 1975;Klein-Breteler et al, 1990;Simon et al, 2009) and farm eels (Wickstro¨m et al, 1996;Pedersen, 1998Pedersen, , 2000Pedersen, , 2009Simon et al, 2013). The annual length increases and survival rates in the stocked eels vary strongly between the stocking environments, the stocking materials (farm and glass eels), the stages (smaller and larger eels) and times after stocking (Bisgaard and Pedersen, 1991;Pedersen, 1998;Lin et al, 2007;Simon et al, 2013;Simon and Do¨rner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…according to Simon et al (2009) the growth and mortality of European glass eel Anguilla anguilla 192 days after marking with oxytetracycline and alizarin red S were not significantly different between the two treatments and not different to the unmarked A. anguilla. The study provided evidence that both marking methods (OTC and ARS) fulfill the capturerecapture assumption of no effect on growth and survival within the glass-eel A. anguilla stage.…”
Section: Discussionmentioning
confidence: 86%
“…In this study ARS showed eight months permanence. According to Simon et al (2009) fish marks with ARS and oxytetracycline were clearly visible after a period of two years in specimens of Anguilla anguilla. The visibility of the marks eight months after marking definitely indicates that the chosen methods allocate for recognition of released individuals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Batch marking by immersion in chemicals that fluoresce under UV light and bind to the growing edge of the otolith, allows the marking of large numbers of juveniles and young fish. Once an adequate treatment has been defined (Wright et al, 2002;Taylor et al, 2005), it generally leads to good mark retention minimum mortality, and is less-time consuming in comparison with other marking methods (Simon et al, 2009). Otolith marks have been produced in juvenile fishes using chemicals such as oxytetracycline hydrochloride (OTC) (McFarlane and Beamish, 1987), alizarin complexone (ALC) (Reichert et al, 2000), alizarine red (ALR) (Simon et al, 2009) and calcein blue (Bumguardner and King, 1996), among others.…”
Section: Introductionmentioning
confidence: 98%